Automatic Construction by Contour Crafting Technology - Mohammad Reza Khorramshahi; Ali Mokhtari (Emerging Science Journal, 2017)
Contour Crafting is a novel technology in construction industry based on 3D printing that uses robotics to construct free form building structures by repeatedly laying down layers of material such as concrete. It is actually an approach to scale up automatic fabrication from building small industrial parts to constructing buildings. However, there are little information about contour crafting (CC) in current use; present paper aims to describe the operational steps of creating a whole building by the machine reviewing relevant literature. Furthermore, it will represent the advantages of CC usage compared to traditional construction methods, as well as its applicability in construction industry.